“My Passion is Farming as my Profession and a Hobby”. Uncharted Correspondence of Maria Rodziewiczówna from 1908 ― some Additional Facts of the Author’s Biography - Fedorovič, Irena (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The main aim of the research is connected with two postcards and two letters that were sent in 1908 to Helena Hurynowicz by the writer Maria Rodziewiczówna (1864– 1944). These objects were found in the collection of The Lithuanian Literature and Art Archives (Lietuvos literatūros i meno archyvas, F43, ap. 1, b. 46), and identified in 2006. The main theme of this correspondence is about everyday life, even trade and business but not literature. The addressee is not a well-known person, that is Helena Hurynowicz. During Rodziewiczówna’s absence in her manor, Helena’s duty, as we can guess, was to take care of the writer’s house in Hruszczowa (Grodno District).
Keywords: Maria Rodziewiczówna, correspondence, the beginning of the 20th century